Effect of letrozole cotreatment in progestin-primed ovarian stimulation on IVF/ICSI outcomes in POSEIDON group 3 and 4 poor responders: a retrospective cohort study - Luyao Wang; Jiaxin Xie; Yifan Chu; Jiayun Chen; Lei Jin; Jing Yue (European Journal of Medical Research)
Abstract Background For poor ovarian response patients, obtaining higher number of transferable and high-quality embryos is crucial and progestin-primed ovarian stimulation protocol is becoming widespread and constantly improving in this population. Letrozole has shown promise in numerous protocols and individuals. This study aims to evaluate the effect of the early addition of letrozole in progestin-primed ovarian stimulation protocol among expected poor ovarian response patients. Methods This retrospective cohort study was performed in POSEIDON group 3 and 4 patients who underwent in vitro fertilization or intracytoplasmic sperm injection with their first progestin-primed ovarian stimulation protocol from January 1, 2018 to December 31, 2021. Totally 557 patients were enrolled in this research with 189 ovarian stimulation cycles for POSEIDON group 3 patients and 368 ovarian stimulation cycles for POSEIDON group 4 patients. The primary outcome of this study was the cumulative live birth rate and cumulative clinical pregnancy rate, and the second outcomes included the laboratory outcomes and pregnancy outcomes, maternal and neonatal complications also were encompassed. Results In this study, progestin-primed ovarian stimulation protocol combined with letrozole (study group) was associated with a significantly higher number of oocytes for retrieval and maturation [3.0 (2.0, 5.0) vs. 2.0 (1.3, 4.0), P < 0.001; 3.0 (2.0, 5.0) vs. 2.0 (1.0, 3.8), P < 0.001] as well as 2PN embryos [2.0 (1.0, 3.0) vs. 2.0 (1.0, 3.0), P = 0.026] among POSEIDON group 4 patients. In POSEIDON group 3 patients, the letrozole cotreatment did not show an advantage in these indicators. There was no significant difference in both cumulative live birth rate and cumulative clinical pregnancy rate between the study and control group in POSEIDON group 3 and 4 patients. Multivariate logistic regression model showed that significant favorable effects of the number of available embryos on cumulative live birth rate in all included patients. Conclusions These findings indicate that advanced-aged poor ovarian response patients may benefit more from using letrozole as an advantageous adjuvant agent in the progestin-primed ovarian stimulation protocol to obtain more oocytes and embryos in clinical practice. Trial registration This trial was retrospectively registered